The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1109/jphot.2019.2957410
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Support Vector Machine Assisted BOTDA for Temperature Extraction With Accuracy Enhancement

Abstract: Brillouin optical time domain analyzer (BOTDA) assisted by optimized support vector machine (SVM) algorithm for accurate temperature extraction is presented and experimentally demonstrated. Three typical intelligent optimization algorithms, particle swarm optimization algorithm, genetic algorithm and firefly algorithm are explored to optimize the SVM parameters. The performances of optimized SVM algorithms for temperature extraction are investigated in both simulation and experiment under different conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
(23 reference statements)
0
6
0
Order By: Relevance
“…The SVM model with sequential minima optimization (SMO) is used for training and validation on binary classification [40,41] . Aside from SVM-SMO, a naïve Bayes classifier with Bayesian optimization is used to test CMFD performance [42,43] .…”
Section: Methodsmentioning
confidence: 99%
“…The SVM model with sequential minima optimization (SMO) is used for training and validation on binary classification [40,41] . Aside from SVM-SMO, a naïve Bayes classifier with Bayesian optimization is used to test CMFD performance [42,43] .…”
Section: Methodsmentioning
confidence: 99%
“…The hyperplane is the best separator between two predefined classes [15] [16]. The basic principle of SVM is a linear classifier, and then it was developed so that it can work on non-linear problems, namely by incorporating the concept of kernel tricks in high-dimensional workspaces [17]. The SVM kernels used in this research are Linear, Radial Basis Function (RBF), and Polynomial kernels.…”
Section: Data Classification Based On Support Vector Machinementioning
confidence: 99%
“…Recently, it has been found that such a trade-off problem can be solved by introducing machine learning (ML). Among various types of ML, support vector machine (SVM), a supervised machine learning model applicable to classification and regression, has been successfully used in Brillouin fiber optic sensors [17][18][19].…”
Section: Introductionmentioning
confidence: 99%